2019
DOI: 10.3390/nano10010070
|View full text |Cite
|
Sign up to set email alerts
|

Organic-Inorganic Hybrid Materials for Room Temperature Light-Activated Sub-ppm NO Detection

Abstract: Nitric oxide (NO) is one of the main environmental pollutants and one of the biomarkers noninvasive diagnosis of respiratory diseases. Organic-inorganic hybrids based on heterocyclic Ru (II) complex and nanocrystalline semiconductor oxides SnO 2 and In 2 O 3 were studied as sensitive materials for NO detection at room temperature under periodic blue light (λ max = 470 nm) illumination. The semiconductor matrixes were obtained by chemical precipitation with subsequent thermal annealing and characterized by XRD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 80 publications
1
9
0
Order By: Relevance
“…Nanocrystalline SnO 2 and In 2 O 3 were synthesized by the chemical precipitation method and a heteroleptic Ru(II) complex was used as a photosensitizer. A detailed scheme of their synthesis is given in our previous work [14]. Hybrid materials were prepared by adsorption of Ru (II) complex on the surface of semiconductor oxides.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nanocrystalline SnO 2 and In 2 O 3 were synthesized by the chemical precipitation method and a heteroleptic Ru(II) complex was used as a photosensitizer. A detailed scheme of their synthesis is given in our previous work [14]. Hybrid materials were prepared by adsorption of Ru (II) complex on the surface of semiconductor oxides.…”
Section: Methodsmentioning
confidence: 99%
“…The composition and microstructure of the materials obtained were investigated by X-ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HRTEM), energy-dispersive X-ray (EDX) spectroscopy, X-ray photoelectron spectroscopy (XPS), and Brunauer-Emmett-Teller (BET) measurements; the optical properties and thermal stability were studied via ultraviolet/visible (UV/Vis) absorption spectroscopy and thermogravimetric analysis (TGA), respectively, and were discussed in detail previously [14]. Surface spin centers were studied by electron paramagnetic resonance (EPR) spectroscopy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of heterojunctions has been proposed to suppress the recombination of photoexcited electrons and holes, thus leading to the improved performance of the UV-activated SnO 2 gas sensor. To further improve the photoactivated sensor performance of SnO 2 at RT, other materials such as LaOCl [71], polypyridine Ru(II) complexes [72], perovskite methylammonium tin iodide (MASnI3) [65], perylene diimide [73] and reduced graphene oxide [74] have been incorporated with SnO 2 to serve as a photosensitizer to widen the spectrum into visible range or as a separator to prevent the combination of photoexcited electron-hole pairs. Xue group showed that LaOCl-doped SnO 2 hollow spheres exhibited significantly improved selective response to O 2 under UV light illumination at RT, due to improved generation of electron-hole pairs and enhanced oxygen adsorption enabled by oxygen vacancy defect due to the presence of LaOCl dopant.…”
Section: Snomentioning
confidence: 99%
“…They ascribed the enhanced sensing performance to the improved light absorption due to MASnI3, which allowed more photoelectrons transfer from MASnI 3 to SnO 2 , as well as the catalysis of Au nanoparticles. An organic photosensitizer, i.e., heterocyclic Ru(II) complex, has been proposed by Gaskov group to shift the photosensitivity range of SnO 2 towards visible light wavelengths [ 72 ]. The Ru(II) complex enables the sensor to have improved response to detecting NO 2 under periodic illumination with blue (λ = 470 nm), green (λ = 535 nm) and red (λ = 630 nm) light.…”
Section: Photoactivated Metal Oxide Semiconductorsmentioning
confidence: 99%